An antibacterial and odor-removing negative oxygen ion composite additive and its preparation and application

By using antibacterial dewy negative oxygen ion composite additives in gypsum boards, the problem of gloating boards is solved in high humidity regions that are prone to breeding molds and stones in high humidity areas. Ion release and excellent antibacterial properties.

CN118993612BActive Publication Date: 2025-01-24YUTING (SHANGHAI) NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411487378.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Existing negative oxygen ion boards are prone to breed mold in areas with high humidity, affecting their aesthetics and increasing the cost of use. At the same time, the addition of germanium stone leads to agglomeration, poor glue force, large internal stress and prone to cracking in gypsum board.

Method used

A antibacterial dewy negative oxygen ion composite additive is used. Composition, prepare by steps such as grinding and dehydration, to ensure the stability and decentralization of vermiculite, and form a stable glue structure with other raw materials.

Benefits of technology

The antibacterial performance, waterproof performance and negative oxygen ion release stability of the gypsum board are significantly enhanced, and the strength and service life of the board are improved while avoiding the occurrence of crisp cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993612B_ABST
    Figure CN118993612B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and specifically discloses an antibacterial and odor-removing negative oxygen ion composite additive, wherein the raw materials include by mass: 10-20 germanium stone, 1-5 silicon-containing hydroxyapatite, 1-5 hydrated calcium silicate, 1-2 hydroxyl-terminated polydimethylsiloxane, 1-2 emulsifier, 1-3 sodium alginate, and 1-3 sodium propionate. The present invention also discloses a preparation method and application of the above composite additive. The present invention also discloses a gypsum board, wherein the raw materials include: desulfurized gypsum, polyvinyl alcohol, amino-terminated polyamide-amine, calcium phosphate, nano zinc oxide, the above antibacterial and odor-removing negative oxygen ion composite additive, styrene, polyethylene wax, diisopropylbenzene peroxide, sodium bisulfite, pentane, glass fiber, and bamboo fiber. The gypsum board obtained by the present invention has high mechanical strength, is not easy to break, has low production cost, and has good thermal insulation performance, good fire retardant performance, long-term release of negative oxygen ions, and remarkable application effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to an antibacterial and odor-removing negative oxygen ion composite additive and a preparation method and application thereof, and a gypsum board and a preparation method thereof. Background Art

[0002] As consumers' environmental and health awareness increases, negative oxygen ion decorative panels, as a new type of environmentally friendly material, are increasingly used in the field of interior decoration. Negative oxygen ions can purify tiny particles suspended in the air, and the smaller the tiny particles, the more obvious the purification effect, which has a significant effect on improving air quality. However, existing negative oxygen ion panels are very prone to mold growth in areas with high humidity, which not only affects the appearance of the decorative panels, but also seriously erodes the negative oxygen ion panels, resulting in increased use costs.

[0003] Germanium stone is a general term for a class of minerals containing germanium in nature. Germanium stone is cheap and has abundant deposits. Germanium stone can release negative oxygen ions, which have a significant improvement effect on cardiovascular and cerebrovascular system, nervous system, respiratory system and other diseases.

[0004] At present, the main raw materials of decorative gypsum boards for construction include powdered materials and reinforced fibers. However, the addition of germanium not only causes agglomeration, but also poor bonding strength between them, which not only affects the function of negative oxygen ions and causes adverse effects, but also causes greater stress in the gypsum board, which makes it easy to crack during use, seriously affecting the quality and service life of the gypsum board. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an antibacterial and odor-removing negative oxygen ion composite additive and a preparation method and application thereof, as well as a gypsum board and a preparation method thereof.

[0006] An antibacterial and odor-removing negative oxygen ion composite additive comprises the following raw materials by mass: 10-20 parts of germanium stone, 1-5 parts of silicon-containing hydroxyapatite, 1-5 parts of hydrated calcium silicate, 1-2 parts of hydroxyl-terminated polydimethylsiloxane, 1-2 parts of emulsifier, 1-3 parts of sodium alginate and 1-3 parts of sodium propionate.

[0007] Preferably, the emulsifier is at least one of alkylphenol polyoxyethylene ether, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester and poloxamer.

[0008] Preferably, the mesh size of the germanium stone is 400 mesh.

[0009] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0010] S1, mixing germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate and grinding for 5-15 minutes, adding to water, then adding hydroxyl-terminated polydimethylsiloxane and emulsifier and stirring for 10-20 minutes, filtering, vacuum drying, and crushing to obtain a premix;

[0011] S2. Add sodium alginate and sodium propionate into water and stir evenly. Add the premix into the water while stirring, continue stirring for 1-3 hours, filter and dry in vacuum.

[0012] Preferably, in S1, the grinding speed is 1000-5000 r / min.

[0013] The present invention adopts silicon-containing hydroxyapatite and germanium stone for composite grinding, which are fully dispersed with each other, and present a gel structure in water with hydrated calcium silicate, and the system stability is extremely good; further dehydration condensation is carried out with hydroxyl-terminated polydimethylsiloxane, and the wrapping performance of the germanium stone powder is good, and sodium alginate is further cemented on the surface of the dispersed material, which can not only significantly enhance the dispersibility of the germanium stone, make it extremely stable, and effectively enhance the stability of releasing negative oxygen ions, but also can be hydrated during the application process to form more gelled products, enhance the interaction between the raw materials, and improve the reduction of mechanical properties caused by foaming, effectively avoid the occurrence of brittle cracking, and greatly enhance the strength of the gypsum board.

[0014] The raw materials of the invention are non-toxic and non-polluting, can not only release negative oxygen ions for a long time, but also have excellent antibacterial performance.

[0015] The above antibacterial and odor-removing negative oxygen ion composite additive is used as a building material.

[0016] A gypsum board, whose raw materials include, by mass: 100-200 parts of desulfurized gypsum, 1-5 parts of polyvinyl alcohol, 1-2 parts of amino-terminated polyamide-amine, 10-20 parts of calcium phosphate, 5-10 parts of nano zinc oxide, 12-20 parts of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 10-20 parts of styrene, 1-2 parts of polyethylene wax, 0.1-1 part of dicumyl peroxide, 0.1-1 part of sodium bisulfite, 1-2 parts of pentane, 5-15 parts of glass fiber and 1-5 parts of bamboo fiber.

[0017] Preferably, the crystal water content of the desulfurized gypsum is ≤3.8%.

[0018] Preferably, the generation of the amino-terminated polyamide-amine is 4.0-6.0. Amino-terminated polyamide-amine is a dendritic macromolecular polymer, which consists of three different parts: a core, an inner layer and an outer layer (also called an initiating core-branching unit-end group); the so-called generation (gerneration), also known as the number of layers (1ayer), refers to the first layer of branching units grafted on the initiating core, which is called the first generation and is generally represented by G1; another layer of branching units is grafted on the first generation, which is called the second generation and is represented by G2, and so on until the outermost end group.

[0019] The preparation method of the gypsum board comprises the following steps:

[0020] a , ball-mill the desulfurized gypsum to a specific surface area of ​​3500-4000cm 2 / g, to obtain pretreated gypsum;

[0021] b , adding polyvinyl alcohol and amino-terminated polyamide-amine to water, stirring at 70-90° C. for 10-30 minutes, then adding calcium phosphate, nano zinc oxide and the above antibacterial and deodorizing negative oxygen ion composite additive and continuing stirring for 10-20 minutes to obtain a dispersed material;

[0022] c 1. Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersed material and continue stirring for 10-20 minutes. Stir at 80-90℃ for 1-2 hours. Add sodium bisulfite and keep warm for 1-2 hours. Add pentane under nitrogen protection, stir at 80-100℃ for 10-30 minutes. Cool to 1-10℃, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0023] Beneficial effects:

[0024] The gypsum board obtained by the invention has high mechanical strength, is not easy to break, has low production cost, and has good thermal insulation performance, good fire retardant performance, and releases negative oxygen ions for a long time, and has a significant application effect.

[0025] In the present invention, with the cooperation of amino-terminated polyamide-amine, calcium phosphate and zinc oxide, calcium phosphate and composite additives are dispersed uniformly in the system, and the stability in polystyrene is significantly enhanced. Not only is the antibacterial and antimicrobial performance excellent, but also because the amino-terminated polyamide-amine is a dendritic structure, its steric hindrance and charge repulsion can promote the uniform dispersion of polystyrene in the pre-treated gypsum, which can effectively enhance the thermal insulation performance of the product, excellent flame retardant performance, and fully eliminate system stress, improve product strength, reduce cracking rate, and improve its mechanical properties under extreme conditions, thereby improving service life. The low-temperature treatment of the present invention is also conducive to the extension of bamboo fiber, and it is compounded with glass fiber, has strong binding force in the pre-treated gypsum, and further significantly enhances the strength of the gypsum board. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison chart of the breaking loads of the gypsum boards obtained in Example 5 and Comparative Examples 1-2.

[0027] Figure 2 This is a comparison chart of the impact resistance and fire stability of the gypsum boards obtained in Example 5 and Comparative Examples 1-2.

[0028] Figure 3 It is a comparison chart of thermal conductivity and amount of induced negative air ions of gypsum boards obtained in Example 5 and Comparative Examples 1-2.

[0029] Figure 4 It is a comparison chart of the antibacterial rates of the gypsum boards obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0030] The present invention will be further explained below in conjunction with specific embodiments.

[0031] Example 1

[0032] The invention discloses an antibacterial and deodorizing negative oxygen ion composite additive, wherein the raw materials thereof include: 10 kg of 400-mesh germanium stone, 1 kg of silicon-containing hydroxyapatite, 1 kg of hydrated calcium silicate, 1 kg of hydroxyl-terminated polydimethylsiloxane, 1 kg of dehydrated sorbitan fatty acid ester, 1 kg of sodium alginate and 1 kg of sodium propionate.

[0033] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0034] S1, grind the germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate for 5 min at a grinding speed of 1000 r / min, add to 50 kg of water, add hydroxyl-terminated polydimethylsiloxane and dehydrated sorbitan fatty acid ester, stir at a speed of 10000 r / min for 10 min, filter, vacuum dry, and crush to obtain a premix;

[0035] S2. Add sodium alginate and sodium propionate into 50 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 1 hour, filter and dry under vacuum.

[0036] A gypsum board, whose raw materials include: 100kg of desulfurized gypsum with a crystal water content of ≤3.8%, 1kg of polyvinyl alcohol, 1kg of 4.0-generation amino-terminated polyamide-amine, 10kg of calcium phosphate, 5kg of nano zinc oxide, 12kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 10kg of styrene, 1kg of polyethylene wax, 0.1kg of diisopropylbenzene peroxide, 0.1kg of sodium bisulfite, 1kg of pentane, 5kg of glass fiber, and 1kg of bamboo fiber.

[0037] The preparation method of the gypsum board comprises the following steps:

[0038] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3500-4000cm 2 / g, to obtain pretreated gypsum;

[0039] b , adding polyvinyl alcohol and amino-terminated polyamide-amine to 50 kg of water, stirring at 70° C. for 10 min, then adding calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continuing stirring for 10 min to obtain a dispersed material;

[0040] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 10 minutes. Stir at 80°C for 1 hour. Add sodium bisulfite and keep warm for 1 hour. Add pentane under nitrogen protection and stir at 80°C for 10 minutes. Cool to 1°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0041] Example 2

[0042] The invention discloses an antibacterial and deodorizing negative oxygen ion composite additive, wherein the raw materials thereof include: 20 kg of 400-mesh germanium stone, 5 kg of silicon-containing hydroxyapatite, 5 kg of hydrated calcium silicate, 2 kg of hydroxyl-terminated polydimethylsiloxane, 2 kg of Tween 80, 3 kg of sodium alginate and 3 kg of sodium propionate.

[0043] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0044] S1, grind the germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate for 15 min at a grinding speed of 5000 r / min, add them into 100 kg of water, add hydroxyl-terminated polydimethylsiloxane and Tween 80, stir at a speed of 20000 r / min for 20 min, filter, vacuum dry, and crush to obtain a premix;

[0045] S2. Add sodium alginate and sodium propionate into 100 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 3 hours, filter and dry in vacuum.

[0046] A gypsum board, whose raw materials include: 200kg of desulfurized gypsum with a crystal water content of ≤3.8%, 5kg of polyvinyl alcohol, 2kg of 6.0-generation amino-terminated polyamide-amine, 20kg of calcium phosphate, 10kg of nano zinc oxide, 20kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 20kg of styrene, 2kg of polyethylene wax, 1kg of diisopropylbenzene peroxide, 1kg of sodium bisulfite, 2kg of pentane, 15kg of glass fiber, and 5kg of bamboo fiber.

[0047] The preparation method of the gypsum board comprises the following steps:

[0048] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3500-4000cm 2 / g, to obtain pretreated gypsum;

[0049] b , add polyvinyl alcohol and amino-terminated polyamide-amine to 100 kg of water, stir at 90° C. for 30 min, then add calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continue stirring for 20 min to obtain a dispersed material;

[0050] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 20 minutes, stir at 90°C for 2 hours, add sodium bisulfite and keep warm for 2 hours, add pentane under nitrogen protection, stir at 100°C for 30 minutes, cool to 10°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0051] Example 3

[0052] The invention discloses an antibacterial and deodorizing negative oxygen ion composite additive, wherein the raw materials thereof include: 12 kg of 400-mesh germanium stone, 4 kg of silicon-containing hydroxyapatite, 2 kg of hydrated calcium silicate, 1.7 kg of hydroxyl-terminated polydimethylsiloxane, 1.2 kg of alkylphenol polyoxyethylene ether OP-9, 2.5 kg of sodium alginate and 1.5 kg of sodium propionate.

[0053] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0054] S1, germanium stone is mixed with silicon-containing hydroxyapatite and hydrated calcium silicate and ground for 12 min at a grinding speed of 2000 r / min, added into 90 kg of water, hydroxyl-terminated polydimethylsiloxane and alkylphenol polyoxyethylene ether OP-9 are added, stirred at a speed of 12000 r / min for 18 min, filtered, vacuum dried, and crushed to obtain a premix;

[0055] S2. Add sodium alginate and sodium propionate into 70 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 2.5 hours, filter and dry under vacuum.

[0056] A gypsum board, whose raw materials include: 120kg of desulfurized gypsum with a crystal water content of ≤3.8%, 4kg of polyvinyl alcohol, 1.7kg of 4.5-generation amino-terminated polyamide-amine, 12kg of calcium phosphate, 9kg of nano zinc oxide, 14kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 18kg of styrene, 1.3kg of polyethylene wax, 0.7kg of diisopropylbenzene peroxide, 0.2kg of sodium bisulfite, 1.7kg of pentane, 8kg of glass fiber, and 4kg of bamboo fiber.

[0057] The preparation method of the gypsum board comprises the following steps:

[0058] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3600-3800cm 2 / g, to obtain pretreated gypsum;

[0059] b , adding polyvinyl alcohol and amino-terminated polyamide-amine to 70 kg of water, stirring at 85° C. for 15 min, then adding calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continuing stirring for 18 min to obtain a dispersed material;

[0060] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 13 minutes, stir at 88°C for 80 minutes, add sodium bisulfite and keep warm for 100 minutes, add pentane under nitrogen protection, stir at 85°C for 25 minutes, cool to 3°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0061] Example 4

[0062] The invention discloses an antibacterial and odor-removing negative oxygen ion composite additive, wherein the raw materials thereof include: 18 kg of 400-mesh germanium stone, 2 kg of silicon-containing hydroxyapatite, 4 kg of hydrated calcium silicate, 1.3 kg of hydroxyl-terminated polydimethylsiloxane, 1.8 kg of alkylphenol polyoxyethylene ether OP-9, 1.5 kg of sodium alginate and 2.5 kg of sodium propionate.

[0063] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0064] S1, grind the germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate for 8 min at a grinding speed of 4000 r / min, add them into 70 kg of water, add hydroxyl-terminated polydimethylsiloxane and alkylphenol polyoxyethylene ether OP-9, stir at a speed of 18000 r / min for 12 min, filter, vacuum dry, and crush to obtain a premix;

[0065] S2. Add sodium alginate and sodium propionate into 90 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 1.5 hours, filter and dry under vacuum.

[0066] A gypsum board, whose raw materials include: 180kg of desulfurized gypsum with a crystal water content of ≤3.8%, 2kg of polyvinyl alcohol, 1.3kg of 5.5-generation terminal amino polyamide-amine, 18kg of calcium phosphate, 7kg of nano zinc oxide, 18kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 12kg of styrene, 1.7kg of polyethylene wax, 0.3kg of diisopropylbenzene peroxide, 0.8kg of sodium bisulfite, 1.3kg of pentane, 12kg of glass fiber, and 2kg of bamboo fiber.

[0067] The preparation method of the gypsum board comprises the following steps:

[0068] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3600-3800cm 2 / g, to obtain pretreated gypsum;

[0069] b , adding polyvinyl alcohol and amino-terminated polyamide-amine to 90 kg of water, stirring at 75° C. for 25 min, then adding calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continuing stirring for 12 min to obtain a dispersed material;

[0070] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 17 minutes, stir at 82°C for 100 minutes, add sodium bisulfite and keep warm for 80 minutes, add pentane under nitrogen protection, stir at 95°C for 15 minutes, cool to 7°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0071] Example 5

[0072] The invention discloses an antibacterial and deodorizing negative oxygen ion composite additive, wherein the raw materials thereof include: 15 kg of 400-mesh germanium stone, 3 kg of silicon-containing hydroxyapatite, 3 kg of hydrated calcium silicate, 1.5 kg of hydroxyl-terminated polydimethylsiloxane, 1.5 kg of poloxamer 407, 2 kg of sodium alginate and 2 kg of sodium propionate.

[0073] Poloxamer 407 was purchased from Beijing Haifuda Technology Co., Ltd., model Lutrol F127.

[0074] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0075] S1, grind the germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate for 10 min at a grinding speed of 3000 r / min, add them into 80 kg of water, add hydroxyl-terminated polydimethylsiloxane and poloxamer 407, stir at a speed of 15000 r / min for 15 min, filter, vacuum dry, and crush to obtain a premix;

[0076] S2. Add sodium alginate and sodium propionate into 80 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 2 hours, filter and dry under vacuum.

[0077] A gypsum board, whose raw materials include: 150kg of desulfurized gypsum with a crystal water content of ≤3.8%, 3kg of polyvinyl alcohol, 1.5kg of 5.0-generation terminal amino polyamide-amine, 15kg of calcium phosphate, 8kg of nano zinc oxide, 16kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 15kg of styrene, 1.5kg of polyethylene wax, 0.5kg of dicumyl peroxide, 0.5kg of sodium bisulfite, 1.5kg of pentane, 10kg of glass fiber, and 3kg of bamboo fiber.

[0078] The preparation method of the gypsum board comprises the following steps:

[0079] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3600-3800cm 2 / g, to obtain pretreated gypsum;

[0080] b , adding polyvinyl alcohol and amino-terminated polyamide-amine to 80 kg of water, stirring at 80° C. for 20 min, then adding calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continuing stirring for 15 min to obtain a dispersed material;

[0081] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 15 minutes, stir at 85°C for 90 minutes, add sodium bisulfite and keep warm for 90 minutes, add pentane under nitrogen protection, stir at 90°C for 20 minutes, cool to 5°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0082] Comparative Example 1

[0083] The invention discloses an antibacterial and odor-removing negative oxygen ion composite additive, wherein the raw materials thereof include: 15 kg of 400-mesh germanium stone, 3 kg of silicon-containing hydroxyapatite, 3 kg of hydrated calcium silicate, 1.5 kg of poloxamer 407, 2 kg of sodium alginate and 2 kg of sodium propionate.

[0084] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0085] S1, grind the germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate for 10 min at a grinding speed of 3000 r / min, add them into 80 kg of water, add poloxamer 407, stir at a speed of 15000 r / min for 15 min, filter, vacuum dry, and crush to obtain a premix;

[0086] S2. Add sodium alginate and sodium propionate into 80 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 2 hours, filter and dry under vacuum.

[0087] A gypsum board, whose raw materials include: 150kg of desulfurized gypsum with a crystal water content of ≤3.8%, 3kg of polyvinyl alcohol, 1.5kg of 5.0-generation terminal amino polyamide-amine, 15kg of calcium phosphate, 8kg of nano zinc oxide, 16kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 15kg of styrene, 1.5kg of polyethylene wax, 0.5kg of dicumyl peroxide, 0.5kg of sodium bisulfite, 1.5kg of pentane, 10kg of glass fiber, and 3kg of bamboo fiber.

[0088] The preparation method of the gypsum board comprises the following steps:

[0089] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3600-3800cm 2 / g, to obtain pretreated gypsum;

[0090] b , adding polyvinyl alcohol and amino-terminated polyamide-amine to 80 kg of water, stirring at 80° C. for 20 min, then adding calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continuing stirring for 15 min to obtain a dispersed material;

[0091] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 15 minutes, stir at 85°C for 90 minutes, add sodium bisulfite and keep warm for 90 minutes, add pentane under nitrogen protection, stir at 90°C for 20 minutes, cool to 5°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0092] Comparative Example 2

[0093] The invention discloses an antibacterial and deodorizing negative oxygen ion composite additive, wherein the raw materials thereof include: 15 kg of 400-mesh germanium stone, 3 kg of silicon-containing hydroxyapatite, 3 kg of hydrated calcium silicate, 1.5 kg of hydroxyl-terminated polydimethylsiloxane, 1.5 kg of poloxamer 407, 2 kg of sodium alginate and 2 kg of sodium propionate.

[0094] The preparation method of the antibacterial and odor-removing negative oxygen ion composite additive comprises the following steps:

[0095] S1, grind the germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate for 10 min at a grinding speed of 3000 r / min, add them into 80 kg of water, add hydroxyl-terminated polydimethylsiloxane and poloxamer 407, stir at a speed of 15000 r / min for 15 min, filter, vacuum dry, and crush to obtain a premix;

[0096] S2. Add sodium alginate and sodium propionate into 80 kg of water and stir evenly. Add the premix into the water while stirring, continue stirring for 2 hours, filter and dry under vacuum.

[0097] A gypsum board, whose raw materials include: 150kg of desulfurized gypsum with a crystal water content of ≤3.8%, 3kg of polyvinyl alcohol, 15kg of calcium phosphate, 8kg of nano zinc oxide, 16kg of the above-mentioned antibacterial and odor-removing negative oxygen ion composite additive, 15kg of styrene, 1.5kg of polyethylene wax, 0.5kg of dicumyl peroxide, 0.5kg of sodium bisulfite, 1.5kg of pentane, 10kg of glass fiber, and 3kg of bamboo fiber.

[0098] The preparation method of the gypsum board comprises the following steps:

[0099] a 2. Send the desulfurized gypsum into the ball mill and grind it to a specific surface area of ​​3600-3800cm 2 / g, to obtain pretreated gypsum;

[0100] b , add polyvinyl alcohol to 80 kg of water, stir at 80°C for 20 min, then add calcium phosphate, nano zinc oxide, and the antibacterial and deodorizing negative oxygen ion composite additive and continue stirring for 15 min to obtain a dispersed material;

[0101] c , Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersion and continue stirring for 15 minutes, stir at 85°C for 90 minutes, add sodium bisulfite and keep warm for 90 minutes, add pentane under nitrogen protection, stir at 90°C for 20 minutes, cool to 5°C, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

[0102] The size of the gypsum boards obtained in Example 5 and Comparative Examples 1-2 is 1500×600×9.5 mm. The breaking load, impact resistance (recording the highest height without radial cracks on the back of the gypsum board after the free fall impact of a steel ball) and fire stability of the gypsum boards obtained in Example 5 and Comparative Examples 1-2 were tested with reference to GB / T9775-2008 "Paper-faced gypsum board".

[0103] like Figure 1 to Figure 2 As shown, the breaking load, impact resistance and fire stability of the gypsum board obtained in Example 5 are the best, which are better than those of Comparative Examples 1-2 (P < 0.05).

[0104] The steps of Example 5 and Comparative Example 1-2 are c The products that have not yet dried after the intermediate molding are placed in the initial drying crack resistance tester. After blowing air longitudinally for 24 hours at a wind speed of 2.0±0.3m / s under standard test conditions, the crack conditions of the samples are observed. The test is carried out 3 times in total, and the worst case among the 3 tests is taken as the crack resistance result. The products of Example 5 and Comparative Examples 1-2 have no cracks.

[0105] The thermal conductivity of the gypsum boards obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 32064-2015 "Test Method for Thermal Conductivity and Thermal Diffusivity of Building Materials by Transient Planar Heat Source". The amount of induced negative air ions of the gypsum boards obtained in Example 5 and Comparative Examples 1-2 was measured with reference to JC / T 2040-2022 "Negative Ion Function Building Interior Decoration Materials".

[0106] like Figure 3 As shown, the thermal conductivity of the gypsum board obtained in Example 5 is the smallest, and the amount of induced air negative ions is the highest, both of which are better than those of Comparative Examples 1-2 (P < 0.05).

[0107] Since gypsum boards are prone to mold growth in a warm and humid environment when used for interior decoration, the applicant used Aspergillus niger ATCC 16404 as a test strain to test the antibacterial properties of the gypsum boards obtained in Example 5 and Comparative Examples 1-2.

[0108] Aspergillus niger ATCC 16404 was cultured and the bacterial solution concentration was adjusted to 10 7 / mL, 10μL of Aspergillus niger suspension was taken and dropped on the surface of the molding mold respectively, and the raw materials were injected into the molding mold for molding according to the respective steps of Example 5 and Comparative Examples 1-2, and the blank group only used desulfurized gypsum as the raw material to inject into the molding mold for molding. After demolding, each group of samples was immersed in a small conical bottle filled with PBS buffer for 60min, and the immersion process was continued and slowly stirred; then a micro-pipette was used to take 10μL of liquid and coated on the surface of the culture medium plate, and the colonies were counted after culturing in a 37℃ constant temperature box for 48h.

[0109] Antibacterial rate = (number of colonies in the blank group - number of colonies in the experimental group) ÷ number of colonies in the blank group × 100%

[0110] like Figure 4 As shown, the antibacterial and antimicrobial properties of the gypsum board obtained in Example 5 are the most excellent, which are better than those of Comparative Examples 1-2 (P < 0.05).

[0111] The applicant believes that the reasons for the above results are: because the present invention adopts silicon-containing hydroxyapatite and germanium stone to grind together, which are fully dispersed with each other and present a gel structure in water with hydrated calcium silicate, and the system stability is extremely good; further dehydration condensation with hydroxyl-terminated polydimethylsiloxane has good encapsulation performance for germanium stone powder, and further bonding sodium alginate on the surface of the dispersed material can not only significantly enhance the dispersibility of germanium stone, making it extremely stable and effectively enhancing the stability of releasing negative oxygen ions, but also can be hydrated during the application process to form more gelled products, thereby enhancing the interaction between the raw materials, and improving the reduction of mechanical properties caused by foaming, effectively avoiding the occurrence of brittle cracking, and greatly enhancing the strength of the gypsum board. At the same time, in the present invention, with the cooperation of the amino-terminated polyamide-amine, the calcium phosphate and zinc oxide, calcium phosphate and the composite additive are dispersed uniformly in the system, and the stability in polystyrene is significantly enhanced. Not only is the antibacterial and antimicrobial performance excellent, but also because the amino-terminated polyamide-amine is a dendritic structure, its steric hindrance and charge repulsion can promote the uniform dispersion of polystyrene in the pretreated gypsum, which can effectively enhance the thermal insulation performance of the product, excellent flame retardant performance, and fully eliminate system stress, improve product strength, reduce cracking rate, and improve its mechanical properties under extreme conditions, thereby increasing service life; and the low-temperature treatment of the present invention is conducive to the extension of bamboo fiber, and is compounded with glass fiber, has strong bonding in the pretreated gypsum, and further significantly enhances the strength of the gypsum board.

[0112] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An antibacterial and deodorizing negative oxygen ion composite additive, characterized in that: The raw materials include, by mass, 10-20 parts of germanium stone, 1-5 parts of silicon-containing hydroxyapatite, 1-5 parts of hydrated calcium silicate, 1-2 parts of hydroxyl-terminated polydimethylsiloxane, 1-2 parts of emulsifier, 1-3 parts of sodium alginate and 1-3 parts of sodium propionate.

2. The antibacterial and deodorizing negative oxygen ion composite additive according to claim 1, characterized in that: The emulsifier is at least one of alkylphenol polyoxyethylene ether, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester and poloxamer.

3. The antibacterial and deodorizing negative oxygen ion composite additive according to claim 1, characterized in that: The mesh number of germanium stone is 400 mesh.

4. A method for preparing the antibacterial and deodorizing negative oxygen ion composite additive according to any one of claims 1 to 3, characterized in that: The steps include: S1, mixing germanium stone with silicon-containing hydroxyapatite and hydrated calcium silicate and grinding for 5-15 minutes, adding to water, then adding hydroxyl-terminated polydimethylsiloxane and emulsifier and stirring for 10-20 minutes, filtering, vacuum drying, and crushing to obtain a premix; S2. Add sodium alginate and sodium propionate into water and stir evenly. Add the premix into the water while stirring, continue stirring for 1-3 hours, filter and dry in vacuum.

5. The method for preparing the antibacterial and deodorizing negative oxygen ion composite additive according to claim 4, characterized in that: In S1, the grinding speed is 1000-5000 r / min.

6. Use of the antibacterial and deodorizing negative oxygen ion composite additive as claimed in any one of claims 1 to 3 as a building material.

7. A gypsum board, characterized in that: The raw materials include, by mass, 100-200 parts of desulfurized gypsum, 1-5 parts of polyvinyl alcohol, 1-2 parts of amino-terminated polyamide-amine, 10-20 parts of calcium phosphate, 5-10 parts of nano zinc oxide, 12-20 parts of the antibacterial and odor-removing negative oxygen ion composite additive according to any one of claims 1 to 3, 10-20 parts of styrene, 1-2 parts of polyethylene wax, 0.1-1 parts of diisopropyl peroxide, 0.1-1 parts of sodium bisulfite, 1-2 parts of pentane, 5-15 parts of glass fiber and 1-5 parts of bamboo fiber.

8. The gypsum board according to claim 7, characterized in that: The crystal water content of desulfurized gypsum is ≤3.8%.

9. The gypsum board according to claim 7, characterized in that: The generation number of the amino-terminated polyamidoamine is 4.0-6.0 generations.

10. A method for preparing a gypsum board as claimed in claim 8 or 9, characterized in that: The steps include: a , ball-mill the desulfurized gypsum to a specific surface area of ​​3500-4000cm 2 / g, to obtain pretreated gypsum; b , adding polyvinyl alcohol and amino-terminated polyamide-amine to water, stirring at 70-90° C. for 10-30 minutes, then adding calcium phosphate, nano zinc oxide and the antibacterial and deodorizing negative oxygen ion composite additive as claimed in any one of claims 1 to 3, and continuing stirring for 10-20 minutes to obtain a dispersion; c 1. Add styrene, polyethylene wax and diisopropylbenzene peroxide to the dispersed material and continue stirring for 10-20 minutes. Stir at 80-90℃ for 1-2 hours. Add sodium bisulfite and keep warm for 1-2 hours. Add pentane under nitrogen protection, stir at 80-100℃ for 10-30 minutes. Cool to 1-10℃, add pretreated gypsum, glass fiber and bamboo fiber, stir evenly, shape and dry.

Citation Information

Patent Citations

  • Retarding aliphatic water reducing agent and preparation method thereof

    CN110482900A

  • Gypsum plaster board and preparation method thereof

    CN111606683A